Impact of PDO and AMO on interdecadal variability in extreme high temperatures in North China over the most recent 40-year period - Zhang, Guwei; Zeng, Gang; Li, Chun; Yang, Xiaoye (Climate dynamics, 2020)
Based on the 1979–2018 datasets of Climate Prediction Center (CPC) daily maximum air temperature, HadISST, and NCEP-DOE II reanalysis, the impact of Pacific decadal oscillation (PDO) and Atlantic multidecadal oscillation (AMO) on the interdecadal variability in extreme high temperature (EHT) in North China (NC) is investigated through observational analysis and National Center for Atmospheric Research (NCAR) Community Atmosphere Model version 5.3 (CAM5.3) numerical simulations. The observational results show an interdecadal shift in NC’s EHT in approximately 1996 with a cold period from 1983 to 1996 and a warm period from 1997 to 2014. The summer PDO and AMO are both closely related to NC’s EHT, of which AMO dominates. From the cold to warm period, the combination of PDO and AMO changed from a positive PDO (+ PDO) phase and a negative AMO (− AMO) phase to a negative PDO (− PDO) phase and a positive AMO (+ AMO) phase. The shift in the antiphase combination of PDO and AMO plays an important role in the interdecadal transition of NC’s EHT in 1996. PDO could impact NC’s EHT through the Pacific-East Asia teleconnection pattern, and AMO could influence the NC’s EHT through an atmospheric wave train in the midlatitudes of the Northern Hemisphere. During the warm period (− PDO and + AMO), warmer sea surface temperature anomalies (SSTA) in the northern North Pacific (NP) and North Atlantic (NA) could cause anticyclonic circulation anomalies over these two basins. The anticyclonic circulations anomalies over the NP could enhance the anticyclone over NC through the Pacific-East Asian (PEA) teleconnection pattern. It could also cause an easterly wind from the NP to NC which would weaken the upper westerly over NC. The anticyclonic anomalies over the NA, which were parts of the wave train, could affect other sectors of the wave train, resulting in anticyclonic anomalies over NC. The anticyclonic anomalies over NC could strengthen the continental high and weaken the upper zonal westerly, resulting in favorable EHT conditions. During the cold period (+ PDO and − AMO), because of the same atmospheric response mechanism, a westerly wind from NC to NP and a wave train with reversed anomaly centers could be found, causing a cyclonic anomaly over NC that is not conducive to the EHT. A series of numerical simulations using CAM5.3 confirm the above observational results and show that the combination of + PDO and − AMO changing to − PDO and + AMO has a great impact on the interdecadal shift in EHT in NC in 1996. The simulations also show that both + AMO and − PDO can lead the EHT in NC individually, and the impact of AMO on the EHT in NC is dominant.